Diseño de un manual de control interno institucional para la Cooperativa de Ahorro y Crédito Camara de Comercio ltda La Mana provincia de Cotopaxi - Sigcha Suatunce, Gladys Erlinda (2012)
This research was based on an Internal Control Manual which brings together a set of policies, procedures and internal control techniques put in place to the Cooperative Credit Union Chamber of Commerce La Manna, in order to mitigate the risks inherent in the operations, providing reasonable assurance to achieve adequate administrative, operational efficiency, reliability of reporting, proper identification and management of risks faced and compliance with regulatory laws that were applicable….